Gastroprotective Activity of Fruit Ethanolic Extract of Tetrapleura tetraptera on Indomethacin-Induced Ulcer in Rats - Oloyede, H.O.B.; Olugbode, A.E.; Salawu, M.O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2018)
Tetrapleura tetraptera (Schum. & Thonn.) Taub. is an important fruit that has many ethno-medicinal uses such as anti-ulcer and nutritive agent. The present study investigated the gastro-protective activity of ethanolic extract of Tetrapleura tetraptera fruit against indomethacin-induced ulcer in rats. For this study, thirty six rats (150-200 g) were separated into six groups of six rats each. For 14 days before ulcer induction with indomethacin, the animals received once daily oral doses of distilled water (groups 1 and 2), omeprazole 20 mg/kg body weight (group 3), and ethanolic extract of T. tetraptera fruit at doses of 50, 100 or 200 mg/kg body weight (groups 4, 5 and 6 respectively). After the last treatment, all the animals except group 1 were fasted for 18 hours with access to water only and treated with 100 mg/kg body weight of indomethacin to induce ulcer. The animals were sacrificed 6 hours after ulcer induction and the stomach was removed for biochemical and histological analysis. T. tetraptera fruit extract significantly (p < 0.05) decreased gastric secretion volume, mean ulcer index, total acidity, total protein and pepsin secretion relative to indomethacin-induced ulcerated rats. The extract also significantly (p< 0.05) increased mucin content relative to the ulcerated untreated rats. These results were similar to those achieved by pretreatment with omeprazole. The activity of glutathione peroxidase and reduced glutathione concentration in the animals treated with 200 mg/kg body weight T. tetraptera fruit were significantly increased (P< 0.05) compared to the negative control. The fruit extract also significantly reduced (P< 0.05) the concentration of malondialdehyde and myeloperoxidase activity over the ulcerated untreated rats. Similarly, the histological analysis showed that T. tetraptera fruit extract prevented indomethacin-mediated disruption of the mucosal wall of the stomach. This study shows that Tetrapleura tetraptera possesses gastroprotective properties which may be attributed to the presence of flavonoids, phenolics and tannins.